2002
DOI: 10.1185/030079902125000075
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Role of Mammary Ductoscopy

Abstract: Mammary ductoscopy (MD) is an emerging technique that allows direct visualisation of the mammary duct system, and that produces sharp and clear video images and ductal washings for cytological analysis. There is a growing body of evidence that MD may have a role in the management of women with pathological nipple discharge, the guiding of breast conserving surgery for cancer, and the screening of high risk women. Further research is required to confirm these potential applications and the feasibility of its us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 9 publications
1
14
0
1
Order By: Relevance
“…Due to its the high (60-fold) magnification, it can detect anomalies which remain below the threshold of other methods [26,27,28]. Our study confirms that ductoscopy is most often technically feasible.…”
Section: Discussionsupporting
confidence: 72%
“…Due to its the high (60-fold) magnification, it can detect anomalies which remain below the threshold of other methods [26,27,28]. Our study confirms that ductoscopy is most often technically feasible.…”
Section: Discussionsupporting
confidence: 72%
“…Interestingly, our results also demonstrated that TNFα levels were higher in patients on CAPD. Although stimulation by dialysis membranes does not occur in CAPD patients, a decrease in renal clearance and an increase of synthesis may explain this finding [26]. …”
Section: Discussionmentioning
confidence: 99%
“…These deeper lesions can be missed by conventional major duct excision [8,35]. In patients with nipple discharge, the percentage of galactographically detected lesions deeper than 3 cm and ductoscopically detected lesions beyond 4 cm are 20% and 18%, respectively [5,31]. …”
Section: Ductoscopic Visual Diagnosis Sensitivity and Limitationsmentioning
confidence: 99%
“…Saline solution is injected through the working channel of the endoscope for clear visualization of the intraductal space [5] (fig. 1, online supplemental material www.karger.com/?DOI=000355833 ).…”
Section: Ductoscopic Technique and Indicationsmentioning
confidence: 99%